Inclusión de la mujer indígena en el servicio exterior ecuatoriano, un análisis desde la teoría crítica de los derechos humanos y las relaciones internacionales - Santillán Sinchico, Martha Cecilia (2021)
This paper analyzes the inclusion of indigenous women in the Ecuadorian Foreign Service, SEE, from the perspective of the critical theory of international relations and human rights. The normative development that made possible a greater participation of the ethnic diversity of Ecuador in diplomatic work is presented, with special emphasis on the participation of indigenous women, in the period 2012-2018. In addition, the contribution of the indigenous movement in the construction of a plurinational State and also the social impact of the inclusion of indigenous women in the SEE is retrospectively identified. The participation of indigenous women in the Ministry of Foreign Affairs, a traditionally male institution, constitutes an advance. Taking this context into account, the purpose of this research is to review the progress and limitations of this inclusion process in the period 2012 - 2018, as well as to evaluate the social impact of this public policy.